Analyzing Arabic Syntax Through Artificial Intelligence: A Pedagogical Framework - Miftachul Huda (IJAS: International Journal of Arabic Studies, 2024)
This study explores the effectiveness of guided inquiry as a strategy for improving Arabic writing skills among Madrasah Tsanawiyah students. The research involved implementing guided inquiry methods in writing instruction over a semester and assessing its impact on students’ grammar, coherence, and critical thinking. Data were collected through pretest and posttest assessments of students’ writing, along with observational data on classroom interactions and student feedback. Results indicated significant improvements in grammar accuracy, sentence complexity, and essay coherence. Students demonstrated enhanced abilities to organize and develop arguments, use evidence effectively, and express their opinions with greater clarity. The guided inquiry approach also positively influenced students' perceptions of their writing abilities and confidence. Despite these gains, challenges such as difficulties in self-editing and generating ideas without direct guidance were noted.